P-299 Protective Effect of Tacrolimus on DSS-induced Colitis via Direct Activation of TGF-β–Smad Signaling Pathway in Intestinal Epitherial Cells. (February 2017) - Satake, Miwa; Sakuraba, Hirotake; Hiraga, Hiroto; Yoshida, Shukuko; Ota, Shinji; Hasui, Keisuke; Tanaka, Nahoko; Watanabe, Rina; Akemoto, Yui; Ishiguro, Yoh; Fukuda, Shinsaku
Abstract : Background: Dysfunctions of intestinal barriers are reported to play important roles in the pathogenesis of Ulcerative colitis (UC). Cellular component of intestinal barriers is intestinal epitherial cells (IECs). Thus, homeostasis of IECs would be an object to prevent inflammatory bowel disease. Transforming growth factor (TGF)-β plays an important role in maintaining homeostasis of IECs. Calcineurin inhibitors are reported to upregulate TGF-β signaling pathway in renal tissue. Tacrolimus (Tac) is highly effective for steroid-resistant UC. The immunosuppressive function of Tac was reported to inhibit T cell proliferation and induce apoptosis of activated T cells. In addition, it is reported that Tac also suppressed the activity of macrophage and induced apoptosis. However, the effects on IECs have not clarified yet. The aim of this study was to investigate the effects of Tac on TGF-β signal in IECs and to examine its protective effect in an experimental colitis model. Methods: Colitis was induced by feeding of 4% dextran sodium sulfate (DSS) in C57/BL6 mice. We investigated protective effects of Tac with or without anti-TGF-β antibody by measuring body weight, histological assessment of mucosal damages and TdT-mediated dUTP nick end labeling (TUNEL) analysis for apoptosis of IECs. Next, we assessed phosphorylation of Smad2/3 in purified IECs by western blotting (WB) and muptiplex bead assay (MBA). Expression of TGF-β and TGF-β receptors in colonic epithelial cells were assessed by MBA and WB. We also examined whether Tac has direct effects on intestinal epitherial cells (IECs) or not using the intestinal epithelial cell line Caco2. The expression of TGF-β receptor type II (TGF-βRII) mRNA was evaluated by quantitative polymerase chain reaction (qPCR). Results: Treatment with Tac ameliorated mucosal destruction and prevented from weight loss through the reduction of epithelial apoptosis. The protective effect of Tac was partially maintained under anti-TGF-β antibody treatment. The expressions of TGF-βRI and II in purified IECs from Tac-treated mice were upregulated compared with that in vehicle-treated mice. Phospho-Smad2/3 expression at 6 hours after Tac injection was upregulated and the effect was observed despite of anti-TGF-β treatment. The expressions of active TGF-β1, 2, 3 in IECs or lamina propria in Tac-treated mice were not upregulated compared with that in vehicle-treated mice. In Caco2 cells, the expressions of TGF-βRI and II were upregulated in the treatment with Tac. Conclusions: These results indicate that Tac has an protective effect from apoptosis-mediated epithelial injury via activating TGF-βR-Smad pathway.